Manajemen Kurikulum Merdeka Belajar - Satria Budi, M. Hanif; Setio Rini, Nur Hikmah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research was motivated by a new policy in the field of Indonesian education from Nadiem Makarim as Minister of Education of the Republic of Indonesia, namely the Merdeka Belajar curriculum, this policy was also applied to madrasas, integrating the curriculum policy of the Ministry of Education and Culture and Technology with the Ministry of Religion of the Republic of Indonesia. The purpose of this study is to find out how the management of the independent learning curriculum in madrasahs, including how to plan the independent learning curriculum in madrasahs, how to implement the independent learning curriculum in madrasahs, how to evaluate the independent learning curriculum in independent learning in madrasas. This research uses a qualitative approach that is descriptive with a case study method. The objects in this study are the KOM Team, Facilitators, and MTsN 1 Kediri Coordinator. The data collection techniques in this study are in the form of observation, interviews, and documentation. Then the data that has been collected is analyzed using data reduction, data presentation, and conclusions. The results of this study are, 1) The planning process of the Merdeka Belajar curriculum consists of socialization, training, and preparation of KOM (Madrasah Operational Curriculum), 2) The implementation of the Merdeka Belajar curriculum begins with intracurricular learning and co-curricular learning through a project to strengthen the profile of Pancasila students and the profile of Rahmatan Lil 'Alamin, and 3) Evaluation of the Merdeka Belajar curriculum, namely an evaluation consisting of meetings and assessments (diagnostic, formative, summative). The results of Merdeka Belajar's curriculum management research in MTsN 1 Kediri are good, with the Madrasah Operational Curriculum (KOM) as a curriculum developer in MTsN 1 Kediri.